James Joyce and Samaritan hospitality : postcritical and postsecular reading in Dubliners and Ulysses - Russell, Richard Rankin (Edinburgh : Edinburgh University Press, 2023)
The first book-length treatment of Joyce and hospitality.
Frontmatter -- CONTENTS -- PREFACE AND ACKNOWLEDGMENTS -- ABBREVIATIONS -- INTRODUCTION -- 1 HAUNTED BY HOSPITALITY IN "THE DEAD" -- 2 JOYCE, SCRIPTURE, AND AUTOBIOGRAPHICAL RESCUE NARRATIVES -- 3 Rewriting the Good Samaritan Parable: THE FICTIONAL RESCUE NARRATIVES OF "GRACE" AND "CIRCE" -- 4 BLOOM AS STRANGER AND SAMARITAN IN "CYCLOPS," "OXEN OF THE SUN," AND "CIRCE" -- 5 "IN ORTHODOX SAMARITAN FASHION": THE PARABOLIC ENCOUNTER BETWEEN STEPHEN AND BLOOM IN "EUMAEUS" -- 6 HOME TO "ITHACA" AND "PENELOPE": BLOOM'S HOSPITALITY AND STEPHEN AND MOLLY'S REACTIONS -- 7 ENFLESHED ETHICS AND THE RESPONSIBILITY OF THE READER IN THE GOOD SAMARITAN PARABLE AND THE "NOSTOS" OF ULYSSES -- CODA "GO THOU AND DO LIKEWISE": POSTCRITICAL AND POSTSECULAR READING THROUGH A JOYCEAN HERMENEUTICS OF HOSPITALITY -- WORKS CITED -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 15, 2022).
eBooks on EBSCOhost
Keywords: Joyce, James, -- 1882-1941 -- Criticism and interpretation; Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941; Dubliners (Joyce, James); Ulysses (Joyce, James); Hospitality in literature; Good Samaritan (Parable); Literary Studies; Hospitalité dans la littérature.; Bon Samaritain (Parabole); LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Good Samaritan (Parable); Hospitality in literature; Criticism, interpretation, etc